2016
DOI: 10.1159/000449296
|View full text |Cite
|
Sign up to set email alerts
|

Lesch-Nyhan Syndrome: Models, Theories, and Therapies

Abstract: Lesch-Nyhan syndrome (LNS) is a rare X-linked disorder caused by mutations in HPRT1, an important enzyme in the purine salvage pathway. Symptoms of LNS include dystonia, gout, intellectual disability, and self-mutilation. Despite having been characterized over 50 years ago, it remains unclear precisely how deficits in hypoxanthine and guanine recycling can lead to such a profound neurological phenotype. Several studies have proposed different hypotheses regarding the etiology of this disease, and several treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 97 publications
(109 reference statements)
1
41
0
2
Order By: Relevance
“…Mutations in the HPRT1 gene can cause severe neurological and metabolic disorders in humans (Fu et al 2014, Harris 2018. It has been shown that mice carrying a defective gene, as a rule, lack bright phenotypic manifestations (Bell et al 2016). However, during the creation of genetically modified animals with a deletion of the nucleotide triplet, which causes the absence of valine in the eighth position of the amino acid sequence of the protein, we encountered certain difficulties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the HPRT1 gene can cause severe neurological and metabolic disorders in humans (Fu et al 2014, Harris 2018. It has been shown that mice carrying a defective gene, as a rule, lack bright phenotypic manifestations (Bell et al 2016). However, during the creation of genetically modified animals with a deletion of the nucleotide triplet, which causes the absence of valine in the eighth position of the amino acid sequence of the protein, we encountered certain difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that Hprt1-deficient mice models do not have a clinical complex characteristic of patients with Lesch-Nyhan syndrome, these models should be used in studies of brain metabolism (Bell et al 2016) and precli-nical studies of the effectiveness of new treatments for this disease, particularly of gene therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes, the selective removal of teeth is performed reluctantly. 3 Treatments with deep brain stimulation 17 and S-Adenylmethionine 18 has been reported, and these are promising methods for treating self-mutilating behavior associated with LNS. Additionally, pharmacologic approaches to therapy based on the neurotransmitter imbalance and gene therapy have not yet been successful in vivo, but this is a promising direction.…”
Section: Lns Can Be One Of the Causes Of Delayed Development In Childmentioning
confidence: 99%
“…Ведущая симптоматика при синдроме Леша-Нихана связана с неврологической патологией (церебральный паралич, нарушение речи, умственная отсталость), однако развитие подагры и повышенная концентрация мочевой кислоты в моче приводит к МКБ с образованием уратных камней [8,41]. При синдроме Леша-Нихана для уменьшения неврологической симптоматики назначают препараты S-аденилметионина, снижающие уровень трансаминаз, для предотвращения образования уратных камней -обильное питьё и диета, направленные на повышение рН мочи [42,43].…”
Section: синдром леша-ниханаunclassified